Kebijakan Berorientasi Misi untuk Mempromosikan Teknologi Digital dalam Mengatasi Ketimpangan Pendidikan dan Mendorong Pembangunan Inklusif di Brasil - Veronica Honorio Gomes de Souza (Jejaring Administrasi Publik, 2022)
The COVID-19 pandemic's consequences have increased inequality and poverty around the world, making it harder to meet the Sustainable Development Goals. One of the main issues is the lack of education experienced by those who are mostly socioeconomically disadvantaged. Due to the technology gap, many underprivileged kids were left behind during the lockdown and school closure since access to the digital tools and infrastructure required to provide continuity of learning remotely was adopted and accessed unequally. For example, 5.5 million children and teenagers in Brazil didn't have access to education in 2020. The present and future of a generation, their families, and the economic and productive capacity of the entire society are all impacted by such a loss, which enlarges the educational gap that already existed in the nation. This situation demonstrates the necessity for governments to prioritise strong measures to close the digital gap in addition to reopening schools. These policies can encourage learning and inclusion of children and adolescents in the information age, which is influencing new methods of learning, working, and living. As a result, this article analyses the digital education gap in Brazil's context and offers suggestions to the ministry of education. The goal is to direct the creation of well-structured policies to make use of technological opportunities to develop the fundamental educational system. The ideas are based on mission-focused and frame 3 innovation strategies, with a particular emphasis on bolstering digital inclusion in basic education, which is essential to advancing social justice and the SDGs.  Keywords: Mission-Oriented Policy, Digital Technology, Educational Inequality, Inclusive Development